2013
DOI: 10.1371/journal.pone.0054299
|View full text |Cite
|
Sign up to set email alerts
|

The Calcitonin and Glucocorticoids Combination: Mechanistic Insights into Their Class–Effect Synergy in Experimental Arthritis

Abstract: IntroductionPrevious work reported the anti-arthritic synergy afforded by combining calcitonin (CT) and glucocorticoids (GC). Here we focus on the pairing of elcatonin (eCT) and dexamethasone (Dex), querying whether: i) this was a class-effect action; ii) mechanistic insights could be unveiled; iii) the synergy affected canonical GC adverse effects.MethodsUsing the rat collagen-induced arthritis model, different combinations of eCT and Dex, were administered from disease onset to peak (day 11 to 18). Macroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Combination therapy resulted in maintained bone structure and absence of cartilage lesions, similarly to previous sCT and CT monotherapy OA studies [17, 50]. A previous study combining CT with glucocorticoids, instead of NSAIDs, also demonstrated a chondroprotective effect in the CIA model [21], indicating a beneficial effect of inhibiting bone destruction and inflammation on joint integrity in severe inflammatory arthritic conditions.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Combination therapy resulted in maintained bone structure and absence of cartilage lesions, similarly to previous sCT and CT monotherapy OA studies [17, 50]. A previous study combining CT with glucocorticoids, instead of NSAIDs, also demonstrated a chondroprotective effect in the CIA model [21], indicating a beneficial effect of inhibiting bone destruction and inflammation on joint integrity in severe inflammatory arthritic conditions.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we demonstrate that combining naproxen with a KBP added significant improvement over naproxen monotherapy. KBP monotherapy did not have significant effects in most structural parameters, similarly to what has previously been reported for CT monotherapy in the CIA model [21, 49]. This may in part be due to the severity of the disease induction being too aggressive for the KBP to overcome, which can be seen within the time to humane endpoint data.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…or 5 IU/kg b.w. Untreated DM: injection of streptozotocin and nicotinamide Al-Kashi et al ( 73 ) Rat F NI RA CIA eCT 11 Daily for 1 week i.p. 0.3-10 μg/kg b.w.…”
Section: Resultsmentioning
confidence: 99%